Melanocortin-4 receptor gene variants are not associated with binge-eating behavior in nonobese patients with eating disorders. (February 2015) - Gamero-Villarroel, Carmen; Rodriguez-Lopez, Raquel; Jimenez, Mercedes; Carrillo, Juan A.; Garcia-Herraiz, Angustias; Albuquerque, David; Flores, Isalud; Gervasini, Guillermo
Abstract : We aimed to determine whether variability in the melanocortin-4 receptor ( MC4R ) gene, predisposing to hyperphagia and obesity, may also be present in nonobese patients with binge-eating behavior or be related to anthropometric or psychopathological parameters in these patients. The coding region of the MC4R gene was sequenced in nonobese patients with binge-eating behavior diagnosed with bulimia nervosa or binge-eating disorder ( n =77); individuals with severe early-onset obesity ( n =170); and lean women with anorexia nervosa ( n =20). A psychometric evaluation (Eating Disorders Inventory-2 and Symptom Checklist 90 Revised inventories) was carried out for all the patients with eating disorders. In the obesity group, 10 different variants were identified, whereas in the binge-eating patients, only two individuals with bulimia nervosa were found to carry the I251L polymorphism, which did not correlate with weight, BMI, or psychopathological features. We found no evidence that mutations in the MC4R gene are associated with binge-eating behavior in nonobese eating disorder patients.